1974
DOI: 10.1084/jem.139.1.74
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Thymus-Independent Immunocyte Triggering

Abstract: We have suggested before that thymus-independent immune responses to certain antigens are caused by special properties of the antigens concerned, namely that they are B-cell mitogens (1). Actually all thymus-independent antigens (TI) 1 we have tested so far were found to be competent to activate DNA and polyclonal antibody synthesis in nonprimed B cells cultured in vitro (2). Since the TI antigens can directly induce division and differentiation in B cells, it is evident that T-B cells cooperation would not be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
64
0

Year Published

1974
1974
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 208 publications
(65 citation statements)
references
References 33 publications
1
64
0
Order By: Relevance
“…24 Recent studies by Hayashi et al indicate that TLR4 signaling also plays a role during late stages of B-cell development by facilitating the generation of immature or transitional B cells. 14 The present study further demonstrates that early B-cell development is subject to regulation by TLR4 signaling.…”
Section: Synergism Of Lps and Il-7 Signals In The Promotion Of Pre-bcmentioning
confidence: 99%
“…24 Recent studies by Hayashi et al indicate that TLR4 signaling also plays a role during late stages of B-cell development by facilitating the generation of immature or transitional B cells. 14 The present study further demonstrates that early B-cell development is subject to regulation by TLR4 signaling.…”
Section: Synergism Of Lps and Il-7 Signals In The Promotion Of Pre-bcmentioning
confidence: 99%
“…This observation gave ground to the idea that microbial products could contribute to maintain a crucial function of the immune system. In the mouse, naive B cells proliferate and secrete Igs in response to LPS and CpG (11,12), indicating that they express functional TLR4 and TLR9. However, little is known about the distribution of TLRs and the impact of their agonists on mouse naive B cell subsets.…”
mentioning
confidence: 99%
“…Their most common natural or synthetic agonists include peptidoglycan and Pam 3 CSK 4 (TLR1/2), bacterial lipoproteins and MALP2 (TLR2/6), dsRNA and poly(I:C) (TLR3), LPS (TLR4), flagellin (TLR5), ssRNA and imidazoquinolines (TLR7 and TLR8), unmethylated CpG oligodeoxynucleotides (TLR9), and profilin-like molecule (TLR11) (7)(8)(9)(10). It has long been known that certain TLR agonists can deliver B cell stimulatory signals (11,12). Furthermore, Ruprecht and Lanzavecchia (13) demonstrated that TLR stimulation is required along with BCR triggering and T cell help to sustain optimal proliferation and differentiation of human naive B cells.…”
mentioning
confidence: 99%
“…On the role of helper T cells in the genesis of IgM AFC by stimulation with T-dependent antigen, Mäller and his colleagues (3,17) assumed that signal from helper T cells or their factor (s) for B cell activation should be similar to that from ANTIGEN-INDUCED AFC AND MITOGEN-INDUCED AFC 165 B-cell mitogen, although Dutton and Hunter (6), and Schimpl et al (19) regarded the "T-cell-replacing factor" as mediator for the differentiation signal as described. The assumption of Moller's group appears to be corroborated by the fact that nu/nu spleen cells, being devoid of T cells, responded to SRBC under simultaneous stimulation with B-cell mitogen.…”
Section: Discussionmentioning
confidence: 99%